Exchange, contracts, and property-rights enforcement - Gabre-Madhin, Eleni Zaude (International Food Policy Research Institute, 2009)
In this section of the book the action domain is the market for goods and services in the context of agriculture and rural markets in developing countries. The focus of the theoretical chapters and the case studies in Part 2 is on addressing a key development problem, namely, the development of coordinated exchange systems in poor rural areas. The core problem relates to the existence of thin markets and low density of economic activity in these areas, resulting in the failure of competitive markets to be effective and efficient mechanisms for coordinated exchange. The use of nonmarket coordination mechanisms develops from this failure but is not unique to developing countries. Under conditions of market failure and for other reasons, nonmarket coordination mechanisms are also often preferred in the developed nations of the world.